Management of concurrent severe COVID-19 pneumonia and antibody-mediated rejection following kidney transplantation: a case report - Xia, Qiuxiang; Li, Heng; Sun, Kailun; Li, Hanying; Zeng, Xianpeng (Frontiers in Medicine, 2025)
BackgroundDue to its high mutation rate, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has recurrently emerged worldwide in recent years, leading to an increased incidence of rejection following kidney transplantation and a worsened prognosis for recipients. The management of the concomitant occurrence of SARS-CoV-2 infection and rejection in kidney transplant recipients poses significant challenges, with limited available experience on this topic. This study presents a case report highlighting the simultaneous manifestation of severe corona virus disease 2019 (COVID-19) pneumonia and acute antibody-mediated rejection (ABMR) during the early post-transplantation period.MethodsThe recipient underwent the renal transplantation from a deceased donor after brain death and received comprehensive management including antiviral therapy, adjustment of immunosuppressive medications, and relevant supportive care during the course of SARS-CoV-2 infection. In the overlapping period of severe COVID-19 pneumonia and ABMR, we implemented plasma exchange (PE) combined with intravenous immunoglobulin (IVIG) and rituximab treatment, while closely monitoring infection-related indicators and elucidate the impact of PE on SARS-CoV-2 antibodies.ResultsThe administration of PE did not significantly impact the level of SARS-CoV-2 IgG antibody. Meanwhile, the combination of PE, IVIG, and rituximab treatment effectively reversed ABMR without exacerbating SARS-CoV-2 infection.ConclusionThe timely administration of antiviral and anti-rejection therapies in the early stage of renal transplant recipient can lead to favorable outcome in case of SARS-CoV-2 infection and concurrent ABMR.